2019
DOI: 10.1634/theoncologist.2019-0463
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Exercise in Lung Cancer Care: Will Promises Be Fulfilled?

Abstract: Lung cancer remains the leading cause of cancer‐related death worldwide. Affected patients frequently experience debilitating disease‐related symptoms, including dyspnea, cough, fatigue, anxiety, depression, insomnia, and pain, despite the progresses achieved in term of treatment efficacy. Physical activity and exercise are nonpharmacological interventions that have been shown to improve fatigue, quality of life, cardiorespiratory fitness, pulmonary function, muscle mass and strength, and psychological status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 113 publications
2
74
0
2
Order By: Relevance
“…It is important to accurately assess preoperative sarcopenia and physical performance because both can be targeted for treatment before and after surgery with various interventions, including nutritional recommendations and rehabilitation 43–45 . Exercise is a non‐pharmacological intervention that improves fatigue, quality of life, pulmonary function, muscle mass, physical performance, and psychological status of patients with lung cancer 37,38 . In addition, the performance of resistance training and use of nutritional supplements, including branched‐chain amino acids, vitamin D, whey protein, and hydroxymethylbutyrate‐enriched milk, play important roles in the prevention and improvement of sarcopenia, 15 and these interventions may result in improved post‐operative outcomes for frail NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to accurately assess preoperative sarcopenia and physical performance because both can be targeted for treatment before and after surgery with various interventions, including nutritional recommendations and rehabilitation 43–45 . Exercise is a non‐pharmacological intervention that improves fatigue, quality of life, pulmonary function, muscle mass, physical performance, and psychological status of patients with lung cancer 37,38 . In addition, the performance of resistance training and use of nutritional supplements, including branched‐chain amino acids, vitamin D, whey protein, and hydroxymethylbutyrate‐enriched milk, play important roles in the prevention and improvement of sarcopenia, 15 and these interventions may result in improved post‐operative outcomes for frail NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines from the American Cancer Society recommend that cancer survivors engage in regular exercise for at least 150 min/wk [ 4 ]. Recent studies have reported that regular exercise is an effective strategy for improving physical fitness, cardiorespiratory fitness, pulmonary function, muscle mass and strength, health-related quality of life (HRQOL), fatigue, psychological status such as anxiety and depression, and sleep quality in breast, lung, head and neck, ovarian, colorectal, and lymphoma cancer survivors during or after treatment [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Studies of patients with gastric cancer during and after treatment have also shown the beneficial effects of exercise on HRQOL [ 12 , 13 , 14 ] and emotional [ 1 ], social, and role functioning [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This makes research simple and easy to predict indicators attract attention, in order to evaluate the risk of lung injury before and early treatment. At the same time, effective interventions can be implemented early to prevent or avoid the occurrence of RILI [20]. The occurrence of RILI is the result of multiple factors.…”
mentioning
confidence: 99%